Tormenting memories and the moral reasoning of past mistakes in iris murdoch’s bruno’s dream: a socio- psychological approach - Abdulrahman, Nada; Mahmoud, Amel (Humanities Journal of University of Zakho, 2023)
This piece of research examines Iris Murdoch’s novel Bruno’s Dream (1969). The analysis focuses on the main character of this novel Bruno and on his recollection of the memories and mistakes he had committed in the past. A nearly ninety years old man who knows that he is losing his battle against cancer soon, spends most of his days in his room attended by a housekeeper and a nurse. Bruno is often seen drifting into a world of fantasies and illusions contemplating past events and actions among which are two major ones; his infidelity to his wife Janie which might be the reason behind her sickness and death and his tense relationship with his only son Miles caused by a faulty decision Bruno recklessly took once. The analysis, in this piece of research, thoroughly focuses on Bruno’s recollections of these occurrences and his overwhelming sense of regret. In this novel, going into these painful memories is a necessity for Bruno to acquire a new self-realization, to rectify the past mistakes and to redeem himself once and for good before confronting his end. The research paper intends to find answers to specific questions such as; what are the main psychological and social reasons behind Bruno’s infidelity? How could he maintain for years two different relationship, a cold one with his wife and an infatuation with Maureen, his mistress? Can faith in God sooth Bruno’s suffering and pacify him? Is it possible to redeem past sins even if it is late, as with the case with Bruno and his son Miles? The methodological approach of this research is largely based on the socio-psychological studies of Erich Fromm. Those in connection with childhood upbringing, emotional deprivation and the lack of security, the “negative freedom”, and his studies on the “new man” who seeks amendments to his faults. All these socio-psychological ideas are tackled in relation to Bruno’s actions and decisions. The methodological approach also utilizes the strategies of close reading techniques and an in-depth literary analysis in order to address specific intrinsic literary features of the novel.